PENGARUH SISTEM ABSENSI FINGERPRINT TERHADAP KINERJA KARYAWAN ALFAMART DI KECAMATAN KAIDIPANG KABUPATEN BOLAANG MONGONDOW UTARA - Sanggilang, Hastuti; Panigoro, Meyko; Maruwae, Abdulrahim; Mahmud, Melizubaida; Dama, Maya Novrita (Journal of Economic and Business Education, 2025)
The purpose of this study was to determine how much the Fingerprint Attendance System Influences the Performance of Alfamart Employees in Kaidipang District, North Bolaang Mongondow Regency. This study uses a quantitative correlational approach method with a sample of 36 Alfamart Employees. the t-count value for the Fingerprint Attendance System variable is 10,284. t-table is calculated with a statistical significance level of 5%. The t-table value obtained is 1.690. The comparison shows that the t-count value of 10,284 1,690 is greater than the t-table value, then the Significant Value of 0.00 is smaller than 0.05. This leads to the rejection of Ho, which implies a positive and significant influence between the Fingerprint Attendance System and Employee Performance. Regression analysis shows a determination coefficient of 0.757, which indicates that 75.7% of Employee Performance is explained by the Fingerprint Attendance System. This indicates a positive relationship between the Fingerprint Attendance System and Employee Performance.